2007
DOI: 10.1016/j.tate.2006.11.001
|View full text |Cite
|
Sign up to set email alerts
|

The teacher educator as a role model

Abstract: New visions of learning have entered education. This article discusses the consequences for teacher education, and examines modelling by teacher educators as a means of changing the views and practices of future teachers. The results of a literature search and a multiple case study on modelling are discussed. Both the literature search and the case study approach led to the conclusion that we have discovered what is almost a blank spot in both the body of knowledge on teacher education and the actual practices… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
169
0
25

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 395 publications
(195 citation statements)
references
References 24 publications
1
169
0
25
Order By: Relevance
“…The importance of the teacher educator as a role model for the next generation of teachers cannot be underestimated (Smith, 2003;Lunenberg et al, 2007), but there is a current lack of focus within higher education institutions on the identities and roles of teacher educators themselves. Korthagen et al (2005) argue that good teachers do not necessarily become effective teacher educators; they need appropriate training and induction into the range of knowledge and skills required.…”
Section: Teacher Educators' Identitiesmentioning
confidence: 99%
“…The importance of the teacher educator as a role model for the next generation of teachers cannot be underestimated (Smith, 2003;Lunenberg et al, 2007), but there is a current lack of focus within higher education institutions on the identities and roles of teacher educators themselves. Korthagen et al (2005) argue that good teachers do not necessarily become effective teacher educators; they need appropriate training and induction into the range of knowledge and skills required.…”
Section: Teacher Educators' Identitiesmentioning
confidence: 99%
“…The strategy might be productively linked to the use of 'modelling' techniques. For example, Lunenberg et al (2007), describe how the teacher educator might progress from the implicit modelling involved in the 'teach as you preach' approach to a more explicit form of modelling which includes facilitating the translation to the trainees' own varied practices. What is very clear is that in the delivery of ITT for the lifelong learning sector, increasingly, one size will not comfortably fit all.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that "teachers teach as they were taught" (Lunenberg, Korthagen, & Swennen, 2007) and increasingly the educators teaching in modular systems also learned about their discipline in such a manner of delivery. Whilst there are clearly many advantages to modular approaches in tertiary education, other approaches also have their merits.…”
Section: Literature Reviewmentioning
confidence: 99%